If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 9 = 19y + 2 Reorder the terms: 9 + -3y = 19y + 2 Reorder the terms: 9 + -3y = 2 + 19y Solving 9 + -3y = 2 + 19y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-19y' to each side of the equation. 9 + -3y + -19y = 2 + 19y + -19y Combine like terms: -3y + -19y = -22y 9 + -22y = 2 + 19y + -19y Combine like terms: 19y + -19y = 0 9 + -22y = 2 + 0 9 + -22y = 2 Add '-9' to each side of the equation. 9 + -9 + -22y = 2 + -9 Combine like terms: 9 + -9 = 0 0 + -22y = 2 + -9 -22y = 2 + -9 Combine like terms: 2 + -9 = -7 -22y = -7 Divide each side by '-22'. y = 0.3181818182 Simplifying y = 0.3181818182
| -6x=1x-70 | | 3x+7_2=5x-6_3 | | 4cd^7(3c^4d^3)= | | 28=6(5-a) | | 7h-21-2h=8h | | 4a^2-6a+3=0 | | 7-2n+3=4+4n | | 0.5(4x-8x+16)= | | 6m-3=2m+6 | | 16x-5=7-14x | | 15=2x+1+4 | | 16-k=38 | | X+3x=x+x+18 | | 15(8x+2)=11 | | 6t-2+3t+17=10 | | -2x=3x-5x | | 13 = s-4+ 17 | | -2(4x+7)=21 | | (4f)2xf=432 | | 18-(x+2)=-9x | | 42=3y+3y | | 2(2x+1)=2x+8 | | 6m-4=6m | | 2(3x-4+5x)= | | -16=x+3x | | 12=8+.5x | | -2n+3=4n | | 4(35+2)=2(2s-1) | | 3.4x-4.4y=15.4 | | 50-5+-5=5t-105 | | .5x-7y=2 | | Y=1+2x+-1x^2 |